Natural Radioactivity Levels on Surface Water of Nemrut Crater Lake (Bitlis, Turkey) - Kuluozturk, M. F.; Dogru, M. (Polish Acad Sciences Inst Physics, 2015)
Nemrut Crater lake is the world's second largest and largest of Turkey crater lake and its altitude is 2250 m. The aim of this study is to determine radioactivity levels of the lake surface water. In this study water samples were collected from 33 points of the lake surface. The gross alpha and gross beta activity concentrations were determined by using ultra low level alpha/beta counter. The mean gross alpha and beta activity concentrations were found to be 77.69 mBqL(-1) and 115.36 mBqL(-1) respectively. Contour maps were produced for gross alpha and beta concentrations of the lake.
International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 25-29, 2014 -- Antalya, TURKEY
Keywords: Gross Alpha; Sediment; Beta